Vloga socialnih partnerjev pri urejanju plačnega sistema v zasebnem sektorju - Poje, Andreja (Delavci in delodajalci, 2016)
The paper presents the importance of salaries, the pay system in the private sector, its development since gaining independence and the role of the social partners in its regulation. It further shows why there is a lack of transparency in the pay system and suggests the necessary changes which would contribute to its greater transparency and uniformity, thus contributing to a more equitable pay for the work performed.
Keywords: delodajalci; kolektivne delovne pogodbe; plače; plačni sistemi; sindikati; socialno partnerstvo; zasebni sektor